2010
DOI: 10.1016/j.biopsych.2009.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Epidural Prefrontal Cortical Stimulation for Treatment-Resistant Depression

Abstract: Background-Treatment-resistant depression presents a serious challenge to both patients and clinicians. The anterior and midlateral prefrontal cortices play complementary roles in integrating emotional and cognitive experiences and in modulating subcortical regions. Both regions offer a distinct opportunity for targeted antidepressant treatments. We chose to pilot the safety and therapeutic benefits of chronic and intermittent epidural prefrontal cortical stimulation (EpCS) in patients with treatment-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 58 publications
(66 reference statements)
0
65
0
1
Order By: Relevance
“…In addition to the traditional ECT, repetitive transcranial magnetic therapy, magnetic seizure therapy, vagus nerve stimulation (VNS), and deep brain stimulation (DBS) have become alternative nonpharmacological treatment options for many psychiatric patients. Other experimental procedures, such as epidural prefrontal cortical stimulation, are under investigation [11] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the traditional ECT, repetitive transcranial magnetic therapy, magnetic seizure therapy, vagus nerve stimulation (VNS), and deep brain stimulation (DBS) have become alternative nonpharmacological treatment options for many psychiatric patients. Other experimental procedures, such as epidural prefrontal cortical stimulation, are under investigation [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a longitudinal functional MRI study reported MPFC to be a biomarker for risk of relapse in patients with depression, probably, it is related to over activation in response to rumination thoughts ( Farb, Anderson, Bloch & Segal, 2011a). Nevertheless, abnormalities in this region has found to be restored successful after antidepressants treatment (Nahas et al, 2010). Inconsistently, some studies reported increased amygdala metabolism to be associated with depression severity (Abercrombie et al, 1999;Drevets et al, 2002).…”
Section: Description Of Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…A postoperative computed tomography of the head is fused with the preoperative MRI to assure appropriate placement [69]. Kopell et al [69] and Nahas et al [80] have shown the feasibility of these implants. Stimulation was well tolerated, with the expected, yet low, chance of surgical complications of bleeding and infection.…”
Section: Depressionmentioning
confidence: 99%